Morphometric and statistical analysis of the palmaris longus muscle in human and non-human primates - Aversi-Ferreira, Roqueline Ametila Glória Martins de Freitas (2014)
The palmaris longus is considered a phylogenetic degenerate metacarpophalangeal joint flexor muscle in humans, a small vestigial forearm muscle; it is the most variable muscle in humans, showing variation in position, duplication, slips and could be reverted. It is frequently studied in papers about human anatomical variations in cadavers and in vivo, its variation has importance in medical clinic, surgery, radiological analysis, in studies about high-performance athletes, in genetics and anthropologic studies.Most studies about palmaris longus in humans are associated to frequency or case studies, but comparative anatomy in primates and comparative morphometry were not found in scientific literature. Comparative anatomy associated to morphometry of palmaris longus could explain the degeneration observed in this muscle in two of three of the great apes. Hypothetically, the comparison of the relative length of tendons and belly could indicate the pathway of the degeneration of this muscle, that is, the degeneration could be associated to increased tendon length and decreased belly from more primitive primates to those most derivate, that is, great apes to modern humans. In conclusion, in primates, the tendon of the palmaris longus increase fromLemuriformes tomodern humans, that is, from arboreal to terrestrial primates and the muscle became weaker and tending to be missing.